2020
DOI: 10.1002/anie.201915164
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Circularly Polarized Organic Ultralong Room Temperature Phosphorescence

Abstract: Purely organic materials showing room temperature phosphorescence (RTP) and ultralong RTP (OURTP) have recently attracted much attention. However, it is challenging to integrate circularly polarized luminescence (CPL) into RTP/OURTP. Here, we show a strategy to realize CPL‐active OURTP (CP‐OURTP) by binding an achiral phosphor group directly to the chiral center of an ester chain. Engineering of this flexible chiral chain enables efficient chirality transfer to carbazole aggregates, resulting in strong CP‐OURT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
197
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(200 citation statements)
references
References 40 publications
3
197
0
Order By: Relevance
“…Purely organic emitting materials with room-temperature phosphorescence (RTP) have shown great potential in bioimaging, [1][2][3] anti-counterfeiting materials, 4,5 organic light-emitting diodes, [6][7][8] and so on. [9][10][11][12] Accelerating intersystem crossing (ISC) between singlet and triplet excited states and suppressing non-radiative transitions and intermolecular collisions have been proven to contribute to efficient RTP. Several strategies have been reported to obtain efficient RTP based on the above two methods, such as introducing heavy halogen atoms 13,14 or carbonyl groups, [15][16][17] crystallization, [18][19][20][21][22][23] polymerization, [24][25][26][27][28][29][30] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Purely organic emitting materials with room-temperature phosphorescence (RTP) have shown great potential in bioimaging, [1][2][3] anti-counterfeiting materials, 4,5 organic light-emitting diodes, [6][7][8] and so on. [9][10][11][12] Accelerating intersystem crossing (ISC) between singlet and triplet excited states and suppressing non-radiative transitions and intermolecular collisions have been proven to contribute to efficient RTP. Several strategies have been reported to obtain efficient RTP based on the above two methods, such as introducing heavy halogen atoms 13,14 or carbonyl groups, [15][16][17] crystallization, [18][19][20][21][22][23] polymerization, [24][25][26][27][28][29][30] and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Light irradiation at selected wavelength can populate specific excited states, select the emissive state energy, then manipulate the emission probability and the emission lifetime. When a chiral ester chain was linked to the N-position of a carbazole phosphor (Li et al, 2020), an H-type aggregate in the condensed state showed CPL at 369 and 379 nm (g lum ∼0.0031) upon photoexcitation at 365 nm. Moreover, chiral phosphorescence FIGURE 2 | (A) Reversible molecular structure change of spiropyran-modified glutamate gelator between a colorless closed ring state and a blue zwitterionic emissive state toward alternating UV and visible light irradiation, with the related SEM images of SP-LG xerogels (lower part).…”
Section: Irradiation With Lightmentioning
confidence: 99%
“…For example, a helical structure incorporating pyrene units showed strong CPL in solution (g lum ∼10 −2 ) with handedness, which was invertible by changing the solvent from toluene to DMSO (Takaishi et al, 2020). Also, a switch from circularly polarized fluorescence to ultra-long phosphorescence was achieved for a chiral carbazole phosphor (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long afterglow phosphorescent materials, which exhibit persistent luminescence after switching off the irradiation source, 1,2 have recently received exponentially increasing attentions, not only because of the significant scientific advance in understanding the rich excited state properties of the optoelectronic materials but also owing to the substantial promise applications ranging from emergency display, 3,4 information encryption 5,6 and storage 7 to bio-imaging and therapy. [8][9][10] Compared to the inorganic afterglow counterparts, 11,12 metal-free organic afterglow materials have many advantages including the ease synthesis conditions, low production costs, large molecular versatility, excellent substrate compatibilities, and many others.…”
Section: Introductionmentioning
confidence: 99%